KARAKTERISTIK TAFSIR SURAH AL-FĀTIḤAH DALAM KITAB NAẒAM TAṢFIYYAH BAHASA JAWA PEGON KARYA K.H. AHMAD RIFA’I KALISALAK - Rizqiyyah, Siti (AL ITQAN: Jurnal Studi Al-Qur'an, 2022)
This research discusses the characteristics of the Naẓam Taṣfiyyah that interpreting Surah Al-Fātiḥah by K.H. Ahmad Rifa'i Kalisalak. This study is important because writing about interpretations using naẓam and the Javanese Pegon language is carried out to impart information about the importance of using nazam in the medium of interpretation, thus facilitating its delivery. This research is library research that uses a descriptive-analytic method of Naẓam Taṣfiyyah as the primary source. The results of this study show that the Naẓam Taṣfiyyah uses the interpretation’s type of bi al-ra'yi or interpretation based on reason (ijtihad). This was done to adjust the context that existed when the interpreter lived and as a way to answer the problems that occurred at that time. Interpretation of K.H. Ahmad Rifa'i uses a thematic method that discusses one theme in one surah, which is Surah al-Fātiḥah. In addition, this interpretation has a combination tendency, namely the theological (tawhid) trend, and the 'adabi al-ijtima'i (social-society) trend. These two patterns can be seen from his thinking which includes theological statements in the context of the leadership of the Dutch infidels to return to the teachings of the Qur'an and the Prophet Muhammad Sallā Allāhu 'Alayhi wa Sallam.